Annual pattern of plasma melatonin and progesterone concentrations in hair and wool ewe lambs kept under natural photoperiod at lower latitudes in the southern hemisphere - Coelho, L. A.; Rodrigues, P. A.; Nonaka, K. O.; Sasa, A.; Balieiro, J. C. C.; Vicente, W. R. R.; Cipolla-Neto, J. (Blackwell Publishing, 2006)
To study the annual pattern of plasma melatonin and progesterone concentrations in hair [Santa Ines (SI)] and wool [Romney Marsh (RM) and Suffolk (SU)] ewe lambs kept under natural photoperiods at 21 degrees 59'S, 12 ewe lambs (four/breed) were used. For melatonin, blood samples were collected monthly throughout the year at the onset (17:00, 19:00 and 21:00 hr) and end (04:00, 06:00 and 08:00 hr) of the night, and for progesterone the samples were collected in the morning, two to three times a week throughout the year. Plasma melatonin concentrations at different times of the day changed according to the season. In diurnal periods (17:00 and 8:00 hr) no seasonal differences were observed but they became evident in the nocturnal intervals (21:00 and 4:00 hr) and transitional night-day (6:00 hr) times. The patterns of melatonin secretion were higher in winter and autumn than in spring and summer. The patterns of plasma progesterone secretion were affected by interaction between breed and season. There was no seasonal variation in plasma progesterone concentrations for SI females. The progesterone pattern for RM and SU females varied with season. The plasma levels were higher in autumn and winter than in spring and summer. At 21 degrees 59'S hair and wool ewe lambs showed the same annual pattern of plasma melatonin concentration while the annual progesterone profiles were quite different. For SI females this pattern was constant along all seasons and for RM and SU females this pattern was higher during autumn and winter than spring and summer.
Keywords: hair sheep; melatonin; natural photoperiod; Progesterone; seasonal reproduction